IMPACT OF COVID-19: FACULTY SUGGESTIONS REGARDING ONLINE MEDICAL TEACHING - Sabqat, Mashaal; Anbreen Aziz; Tayyeba Iftikhar Mirza; Bushra Adeel (Journal of Ayub Medical College Abbottabad, 2022)
Background: As a result of the SARS-CoV-2 related government lockdown, academic institutions in Pakistan, including medical and dental colleges and universities, had to forgo on-site classes and make an emergency shift to online teaching. This study explores the perspective of the faculty, as a key stakeholder, on ways to increase the effectiveness of online teaching and learning at these medical and dental colleges and universities. Methods: A descriptive cross-sectional qualitative survey was conducted in April-July 2020 in 32 medical and dental colleges of Pakistan. The sample size was not pre-determined and the participants included teaching faculty of both clinical and basic sciences. Data were iteratively collected and analyzed till data and time saturation were achieved. Thematic analysis of data was done by running two coding cycles. All authors ensured analytical triangulation by analyzing the data independently before developing consensus on the subthemes and themes. Results: One hundred and thirty-two medical teachers responded. Data analysis revealed three themes regarding suggestions to improve teaching methods improve assessment and increase the effectiveness of online teaching and learning. The participants suggested supplementing real-time classes with recorded lectures, providing broadband internet services, using assignment-based and active learning strategies, continuous formative assessment, faculty training, and standardization of online teaching by higher authorities. Conclusion: The current study offers actionable steps to decision makers at medical colleges and universities to make online teaching and learning more efficient and valuable, based on the suggestions from their faculty.